1989
DOI: 10.7326/0003-4819-110-9-719
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Validity of Certification by the American Board of Internal Medicine

Abstract: Comparison of findings from the written examination and the professional associate ratings with certification status and original ABIM certification examination scores shows predictive validity of ABIM certification. Further studies are needed to determine if certification status predicts important differences in the care of patients with complex illnesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0
5

Year Published

1989
1989
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(83 citation statements)
references
References 10 publications
1
77
0
5
Order By: Relevance
“…Most of these studies dealt with the ability of the ABIM certifying examination to measure the construct of medical knowledge needed by an internal medicine physician. [1][2][3] More recently, two studies have dealt specifically with the ability of the ITE to predict outcome on the ABIM certifying examination. 4,5 Both studies demonstrated a significant correlation between the ITE and the ABIM certifying examination scores.…”
mentioning
confidence: 99%
“…Most of these studies dealt with the ability of the ABIM certifying examination to measure the construct of medical knowledge needed by an internal medicine physician. [1][2][3] More recently, two studies have dealt specifically with the ability of the ITE to predict outcome on the ABIM certifying examination. 4,5 Both studies demonstrated a significant correlation between the ITE and the ABIM certifying examination scores.…”
mentioning
confidence: 99%
“…Observamos que la posibilidad de aprobar el examen era casi 3 veces mayor si el aspirante provenía de un programa acreditado por la SAP por el máximo plazo (5 años), lo cual resalta la importancia que esta actividad tiene para garantizar la calidad de la enseñanza. 8,9 No hemos encontrado estudios que exploren específicamente el aspecto relacionado con la edad y el resultado del examen de certificación. En un estudio desarrollado en Estados Unidos, donde se evalúan predictores de la capacidad profesional de médicos graduados fuera de ese país, Kanna y col. encuentran que, a menor edad de los médicos residentes, se verifican mejores calificaciones durante su residencia en medicina interna, y especulan con la posibilidad de que los mayores tuvieran destrezas fuertemente internalizadas adquiridas fuera del país, que difícilmente se adapten al estándar estadounidense.…”
Section: Resultsunclassified
“…Certification by the ABMS and participation in continuing certification has been shown to translate into improved patient outcomes in non-EM specialties. [9][10][11][12][13][14][15][16] The criterion standard for MK assessment in EM has traditionally been certification by ABEM, which consists of a qualifying examination delivered in MCQ format and an oral examination. However, we were unable to locate any data on the effect ABEM certification has on patient-centered outcomes (e.g., Kirkpatrick level 4 evaluations).…”
Section: Multiple-choice Questions (Mcq) Testingmentioning
confidence: 99%